Hubungan Dukungan Sosial Keluarga dengan Efikasi Diri Merawat Bayi Baru Lahir pada Ibu Primipara - Umbu Nggiku Njakatara; Domianus Namuwali (JURNAL KESEHATAN PRIMER, 2022)
Introductions: A mother's self-confidence or self-efficacy is self-confidence in her ability to show behavior that leads to the results to be achieved. Increasing the self-confidence of a primiparous mother requires support from the closest family, especially partners in increasing the mother's ability to care for newborns. The aims of this research was to estimate family social support and self-confidence correlation for primiparous mothers to carry out newborns. Methods:  A cross-sectional design was used in this research. 54 primiparous mothers as total sample of the study, and determined by the total sampling technique. The PSES (Parental Self-Efficacy Scale)   instrument was used to establish the self-efficacy of primiparous in caring for newborns, and Family Social Support Questionnaire to show family social support for primiparous mothers. The data was analized with person correlation test with a significance level of p value <0.05. Results: Study result was showed a significant correlation between family support and self-efficacy of primiparous mothers, with p value <0.024. Conclusion: It was founded a significant correlation between primiparous mother self-efficacy and family social support in caring for newborns. Keywords: Family support; mother's self-efficacy; social support